2021
DOI: 10.1111/trf.16344
|View full text |Cite
|
Sign up to set email alerts
|

Occult and active hepatitis B virus detection in donated blood in São Paulo, Brazil

Abstract: Background The present study determined the HBV antigen, antibody, and DNA status in blood donations deemed to be HBV positive. Individuals with an occult HBV infection (OBI), defined as being positive for HBV DNA but negative for HBV surface antigen (HBsAg), as well as those with active infection (HBsAg‐positive), were identified and characterized. Study Design and Methods From a total pool if 198,363 blood donations, we evaluated in a cross‐sectional study, 1106 samples that were positive in screening tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The prevalence found for OBI was 6.1%; this is considered high in comparison to another study conducted among blood donors performed in São Paulo in which the prevalence was 0.6% [ 37 ]. It has been shown in many studies that rates for OBI vary in different populations according to the endemicity of HBV infection.…”
Section: Discussionmentioning
confidence: 52%
“…The prevalence found for OBI was 6.1%; this is considered high in comparison to another study conducted among blood donors performed in São Paulo in which the prevalence was 0.6% [ 37 ]. It has been shown in many studies that rates for OBI vary in different populations according to the endemicity of HBV infection.…”
Section: Discussionmentioning
confidence: 52%
“…According to a WHO report, countries around the world employ three main strategies for screening blood donors for HBV: (a) 56% (98/176) of countries employ HBsAg testing; (b) 17.6% (31/176) of countries employ both HBsAg and anti -HBc testing (with 5 countries, including selective anti -HBc testing); (c) Another 8 countries implemented a 3-testing strategy that included selective anti -HBc testing [ 19 ]. In São Paulo, Brazil, 0.6% (6/976) of anti -HBc positive blood donors who were negative for HBsAg and 6 MP-NAT were positive for single-sample HBV DNA testing [ 20 ]. This rate is half as low as that found in Shandong Province, China, where 1.2% (2/164) of donors were positive for HBV DNA testing.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding OBI, we only detected one case in 52,574 donations using ID-NAT-HBV ( Table 3 ). Recently, González-Santos et al detected 1 in 66,137 in Mexico City [ 10 ] ( Table 6 ), Dodd et al, in the USA, detected 1 in 67,974 [ 36 ] and Nishiya et al reported 1 in 33,121 donations in Brazil [ 37 ].…”
Section: Discussionmentioning
confidence: 99%